Trabalho, subjetividade e identidade dos Institutos Federais de Educação, Ciência e Tecnologia: análise de um caso sui generis - Loureiro, Thiago (2020)
The present study sought to understand the organizational identity of IFSP São Carlos, as well as the work and subjectivity of its professors. To this end, it preliminarily resorted to the history of the RFEPT in the different historical moments of the country, and then focused on the most recent model – the IF, conceived and implemented since 2008, during Lula government. This is a case study with qualitative guidance based on Psychodynamics at Work, Psychosociology and Social Psychology. To address the professor’s work and subjectivity, the study included the application of a survey to a total of thirty-three respondent professors, followed by ten semi-structured interviews with members of the faculty from all branches of IFSP São Carlos. In addition, two administrative employees were also interviewed. The twelve interviews were analyzed through content analysis. When analyzing IFSP São Carlos, it was found that the institution’s constitution, since its implantation, as CEFET, it was related to political aspects which involved federal, municipal and UFSCar management. In this sense, the intrinsic relationship with UFSCar, makes IFSP São Carlos a unique case of the Network. In the institution, two moments of changes in its development and its organizational identity were identified, both permeated by disputes and interest and, specifically, by power relations between the technological branches, as well as their political correlations. This took place when the company moved to its own headquarters in 2016 and with the effectuation of High School activities integrated in 2017, which had not yet been implemented. It was noted idiosyncrasies and ambivalences related both to the multiform demands of work, as well as to the management tools that guide the teaching workload. Although it was not the motto of the study, voices from administrative servants were accessed, a fact that led to the understanding of an intensified work widespread in the institution, some with serious consequences for their subjectivism, as well as for psychic and psychosomatic health. The current political and governmental moment in the country, antagonistic to the education project that generated the FIs, also contributed to such developments. Although the pleasurable experiences of the faculty and institutional careers are evident, they do not immunize these professional from psychic burden derived from a complex and permeated by contradictions daily life. However, the current moment of IFSP São Carlos, in its new facilities and with the cultural change resulting from the consolidation of Integrated High School, has brought IFSP São Carlos closer to the beacons recommended by the RFEPT and a possible identity better suited to its legal conception – politics, although subject to forges and disputes. It is concluded that the transitions and metamorphoses of the IFSP São Carlos organizational identity occurred interspersed with disputes, idiosyncrasies and ambivalences. Such identity– organizational changes reverberate in the socially assigned and subjectively appropriate identities of professors. These also metamorphose, in some cases, in a sublimatory way, in others, giving rise to suffering, conflicts, stress, stress and/or illnesses. In other words, the hybridity and metamorphoses of IFSP São Carlos have repercussions and generate different implications for the idiosyncrasies and contradictions of teaching subjectivities.